Relationship between arctan and arccot

From specialfunctionswiki
Jump to: navigation, search


The following formula holds: $$\mathrm{arctan}(z) = \mathrm{arccot}\left( \dfrac{1}{z} \right),$$ where $\mathrm{arctan}$ denotes the inverse tangent and $\mathrm{arccot}$ denotes the inverse cotangent.


Let $y = \arctan \left( \dfrac{1}{z} \right)$. Then since arctan is the inverse function of tangent, $$\tan(y)=\dfrac{1}{z}.$$ By the definition of cotangent, we get $$\cot(y)=z.$$ Since $\mathrm{arccot}$ is the inverse function of $\cot$, take the $\mathrm{arccot}$ of each side to get $$y = \mathrm{arccot}(z).$$ Therefore we have shown $$\arctan \left( \dfrac{1}{z} \right) = \mathrm{arccot}(z),$$ as was to be shown.